Self Efficacy, Capital, Return, and Risk Shaping Students’ Investment Interest: Keyakinan Diri, Modal, Imbal Hasil, dan Risiko Mempengaruhi Minat Investasi Mahasiswa - Hikmah, Syahrur Romadhonil; Hariyanto, Wiwit (Indonesian Journal of Innovation Studies, 2025)
General Background: Investment awareness among students has become increasingly vital as they represent a key demographic in developing future investors in Indonesia. Specific Background: Despite the growing accessibility of investment platforms, students’ willingness to invest remains low, particularly due to psychological and financial barriers. Knowledge Gap: Previous studies have not comprehensively examined the joint role of self-efficacy, minimum capital, perceived return, and risk in explaining students’ investment interest, especially among Generation Z learners. Aims: This study investigates how these four variables contribute to students’ investment interest at Muhammadiyah University of Sidoarjo. Results: Using a quantitative approach and multiple linear regression analysis with 60 respondents, the findings reveal that self-efficacy, minimum capital, perceived return, and risk each significantly relate to investment interest. The model explains 49.2% of the variation in investment interest. Novelty: The inclusion of self-efficacy as a behavioral determinant under the Theory of Planned Behavior framework provides a deeper understanding of students’ investment motivation. Implications: The study highlights the need for targeted financial education and university-based investment literacy programs to strengthen confidence and rational decision-making among young investors. Highlights: Self-efficacy and perceived return are strong predictors of investment interest. Minimum capital accessibility motivates students’ investment participation. Risk perception moderates investment intentions among young investors. Keywords: Self Efficacy, Minimum Capital, Perceived Return, Risk, Investment Interest